Pengaturan Dewan Pengawas KPK dan Implikasi Terhadap Indepedensi Komisi Pemberantasan Korupsi dalam Sistem Ketatanegaraan Republik Indonesia - Candra Erens Bira; Saryono Yohanes; Hernimus Ratu Udju (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2024)
This study aims to analyze how the existence of the Supervisory Board affects the KPK's position as an independent institution. In addition, this study also identifies obstacles in the implementation of the Supervisory Board regulation that may impact the effectiveness of the KPK. The method used in this research is normative legal research that relies on document studies and legislation related to the KPK as well as the theory of constitutional law. The result of this research is that the regulation of the KPK Supervisory Board, especially in granting licenses for KPK legal actions, has the potential to weaken the independence of the KPK. The duties of the Supervisory Board, which enter the realm of pro justicia, lead to unclear roles and bureaucratic obstacles in the investigation process. This has implications for reducing the effectiveness of the KPK in eradicating corruption in Indonesia.